Genetic study of Red Maasai sheep and their Dorper crossbred’s performance in sub-Saharan Africa - Oyieng, Edwin P. (Justus-Liebig University of Gießen, 2025)
The aim of this thesis was to study the performance of the Red Maasai sheep, the Dorper sheep and their crosses reared in a semi-arid environment. The study involved the analysis of reproduction parameters, survival of lambs and ewes length of productive life, the impact of heat stress on growth, and developed novel resilience phenotypes for the sheep population. The main breed groups in the breeding program comprised pure Dorper (DDDD), pure Red Maasai (RRRR), 75%Dorper-25%Red Maasai (DDDR) and 50%Dorper-50%Red Maasai – F1 (DDRR). R and ASReml-R software were used to evaluate reproduction parameters. Survival of lambs and the length of productive life of ewes were analysed using Cox and Weibull hazard models of the Survival Kit Version 6.12 software. Random regression models fitted with reaction norm functions were used to assess the impact of heat stress on growth and derive novel resilience phenotypes for growth in response to different levels of heat stress. Information generated through studying the reproductive performance of the flock is presented in Chapter 2. The pure Red Maasai sheep had significantly lower values for average age at first lambing (AFL), ewe birth weight (EBWT), ewe weaning weight (EWWT), litter birth weight (LBWT) and litter weaning weight (LWWT) compared to other breeds studied. The birth type (single or twins), sex of the lamb and parity in which the lambs were born significantly affected ewes’ birth and weaning weights. The overall heritability estimates of AFL (0.09±0.04) and LI (0.00±0.01) were not significant (P>0.05) while the heritability estimates for EBWT (0.38±0.04), EWWT (0.23±0.03), LBWT (0.19±0.03) and LWWT (0.09±0.02) were significant (P<0.05). The repeatability estimates were low for LBWT (0.25), LWWT (0.16) and that of lambing interval (LI) was near zero. Genetic and phenotypic correlations showed strong positive relationships between ewe and lamb weights. The Red Maasai had higher genetic and phenotypic correlations and genetic gains for the traits studied compared to the pure Dorper while the DDRR breed combination had a higher genetic gain among the crosses. LI had negative genetic correlations with LBWT and LWWT while AFL had positive genetic correlations with LBWT and LWWT. The phenotypic trends for AFL and LWWT showed a negative association with rainfall index over the years. Chapter 3 presents the results of pre- and post-weaning lamb survival to yearling, and ewes length of productive life. The pure Red Maasai lambs and ewes had better pre-weaning lamb survival rates and better productive life compared to the other breeds. Overall, 95% and 83% of lambs survived to weaning (90 days) and yearling (365 days), respectively. The Red Maasai lambs had the lowest mortality rates (2%) while Dorper lambs had the highest postweaning mortality (24%) among the breeds. Lamb survival was significantly influenced by the season of birth, parity in which the lambs were born, birth type (single or twin) and birth weight. Single born lambs, those born during the wet season, offspring of multiparous ewes, and those having higher birth weights (>3kg) were associated with lower mortality risks. Ewe longevity was significantly affected by the breed, age at first lambing, parity and birth weight. Ewes of DDDR breed combination and those that had heavier birth weights (>3Kgs) had the highest risk of being culled, while ewes with a higher age at first lambing (>975 days old) and more than one lambing were less likely to be culled. Pre-weaning heritability estimates for survival (0.10–0.14) were higher than post-weaning estimates (0.01-0.05). The Red Maasai had the highest genetic gain for pre-weaning survival (-0.026) compared to DDDR (-0.018), F1 (-0.011), and Dorper (-0.012). General weakness, often due to poor nutrition, posed the highest risk for of lambs dying post-weaning (12.99 risk ratio), followed by diseases like enterotoxemia and sheep pox (6.006 risk ratio). The impact of heat stress on the growth of sheep and novel resilience phenotypes for growth are presented in Chapter 4. Heat stress, expressed as Temperature-Humidity Index (THI), significantly affected the growth of the sheep. The Red Maasai sheep had a higher tolerance for heat stress compared to the other breeds studied. The THI break points, when growth is affected by heat stress, were 78.75, 78.71, 78.42 and 77.93 for RRRR, DDDD, DDRR and DDDR respectively. At the THI break point, the growth rate declined at a rate of 0.06 Kgs, 0.09 Kgs, 0.05 Kgs and 0.15 in live weight gain per unit change in THI for RRRR, DDDD, DDRR and DDDR respectively. Random regression models fitted with reaction norm functions were used to develop two resilience phenotypes namely: Response and Stability. These resilience phenotypes were developed at THI 70 (representing low/no heat stress) and THI 85 (representing high heat stress). The breed, sex, type of birth, dams’ parity and season of birth significantly affected the stability of growth at low and high heat stress. Genetic correlations of resilience phenotypes at THI 85 with pre-weaning live weight gain (LWG1) were antagonistic and significant but not for post-weaning live weight gain (LWG2). Strong positive genetic and phenotypic correlations existed between response and its corresponding stability trait. The heritability estimates of resilience traits ranged from 0.12 for Response at THI 70 to 0.16 for Stability at THI 85. The better lamb survival and ewe longevity, and high tolerance to heat stress of the Red Maasai breed are an indication of their suitability for the harsh environment. Crossbreeding of the Red Maasai with Dorper has the potential to optimize growth and reproductive efficiency in the semi-arid environment. The moderate heritability estimates for resilience phenotypes in the population studied highlight opportunities for selective breeding to enhance resilience for growth under the changing climatic conditions. Context-specific improved animal management practices can increase the survival of lambs, improve their reproductive performance and reduce the impact of heat stress on growth.